Gambaran Nilai Professional Behaviours Keperawatan Mahasiswa Tingkat II Program Diploma AKPER Yayasan Keperawatan Yogyakarta - Annisa, Rully (Fakultas Kesehatan Universitas Muhammadiyah Cirebon, 2018)
Background: Professional behaviors are one of the elements that nurse students must have in addition to clinical knowledge and skills, to become professional nurses when they have been in the workplace and nursing professionalism for the present is getting better. The purpose of this study: This study to determine the description of the professional behavior of students in the second level of DIY nursing program AKPER YKY. Research Method: This research use descriptive research method. The sampling technique in this study used incidental sampling amounted to 72 active students. Data were collected using Shieffietd Peer Review Assessment (SPRAT) questionnaire with self assessment technique consisting of 23 Likert-scale questions. Results: The results of the study showed that the value of professional behaviors of nursing respondents consisted of low category 5 students, medium category 1 students, high category 33 students, very high category 33 students. Conclusion: The results of the study showed that the value of professional behaviors of nursing respondents consisted of high category 33 students, very high category 33 students. From the results of professional behaviour values ??can be used as an evaluation for institutions and students on the value of professional behaviour owned, and used as input for the preparation of curriculum about the value of professional behavior. Keywords: Value of Professional Behavior, Student, Nursing Diploma Program